In Silico Docking, Pharmacokinetic, and Toxicological Profiling of Ziziphus budhensis Leaves Phytochemicals as Potential Aldose Reductase Inhibitors - Bharati, Samjhana; Parajuli, Nirmal; Shrestha, Timila; Maharjan, Binita; Marasini, Bishnu P.; Adhikari Subin, Jhashanath; Devkota, Hari Prasad; Dall’Acqua, Stefano; Shrestha, Ram Lal Swagat (Amrit Research Journal, 2025)
Diabetes mellitus is a long-term metabolic disorder associated with hyperglycemia-induced complications, mostly regulated through aldose reductase (AR), a key enzyme in the polyol pathway. Therefore, inhibition of AR has become an emerging therapeutic strategy to manage diabetes-associated complications linked to carbohydrate metabolism. In this study, 29 phytochemicals from Ziziphus budhensis leaves were computationally screened against AR enzymes (PDB ID: 1IEI) using molecular docking and pharmacokinetic analysis. Among the screened compounds, Eriodictyol-7-O-glucoside (M01), Epicatechin (M02), Euscaphic acid (M03), and Catechin (M04) exhibited the highest binding affinities with docking scores of -11.3, -10.3, -10.1 and -9.9 kcal/mol, respectively, exceeding that of the native inhibitor Zenarestat (-9.7 kcal/mol). These compounds showed multiple hydrogen-bond interactions with key active-site amino acid residues, suggesting strong and favourable binding interactions in the polyol pathway. The ADMET profile of these hit molecules highlighted that compounds M02 and M04 possess the best drug- likeness, oral bioavailability, and balanced physicochemical properties, and the least toxic characteristics, compared to native and other top ligands, strengthening their potential as safe and effective AR inhibitors. Therefore, the molecules M02 and M04 are recommended as possible AR inhibitors, based on docking and pharmacokinetic predictions. This study facilitates a good theoretical foundation for developing plant-based inhibitors targeting AR for diabetes management.